Sila‐α‐galbanone and Analogues: Synthesis and Olfactory Characterization of Silicon‐Containing Derivatives of the Galbanum Odorant α‐Galbanone. Issue 26 (5th August 2014) - Dörrich, Steffen; Ulmer, Anna; Mahler, Christoph; Burschka, Christian; Baus, Johannes A.; Tacke, Reinhold; Chai, An; Ding, Changming; Zou, Yue; Brunner, Gerhard; Goeke, Andreas; Kraft, Philip
Abstract: Silicon compounds1b –3b are sila‐analogues of the galbanum odorants α‐galbanone (1a ), α‐spirogalbanone (2a ), and nor ‐α‐galbanone (3a ), respectively. Sila‐α‐galbanone (1b ), sila‐α‐spirogalbanone (2b ), and sila‐ nor ‐α‐galbanone (3b ) were synthesized in multistep syntheses in isomerically pure form, starting from Me2 SiCl2, (CH2 =CH)2 SiCl2, and Me2 (CH2 =CH)SiCl, respectively. Hydroformylation of vinylsilanes, followed by either ring‐closing aldol condensation or ring‐closing alkene metathesis, were the key steps in these syntheses. The C/Si pairs1a /1b, 2a /2b, and3a /3b were studied for their olfactory properties. All compounds possess green‐fruity galbanum‐type odors with pineapple aspects and thus are olfactorily related. However, sila‐analogues1b –3b were found to be weaker than the corresponding parent carbon compounds1a –3a . This effect is most pronounced for the C/Si pair2a /2b as indicated by the odor thresholds of 0.023 ng L –1 air (2a ) and 3.8 ng L –1 air (2b ). However, due to their higher molecular mass, the silicon compounds are less volatile and thus more substantive in functional applications. In contrast to the stable 5‐silacyclohex‐1‐enes1b and2b, the 4‐silacyclopent‐1‐ene3b shows a limited chemical stability. For compound3a an extremely low odor threshold of 0.0087 ng L –1 air was measured, and the silicon analogue3b with an odor threshold of 0.085 ng L –1 air is the sila‐odorant with the lowest odor threshold measured so far. Abstract : Sila‐α‐galbanone, sila‐α‐spirogalbanone, and sila‐ nor ‐α‐galbanone (sila‐analogues of α‐galbanone, α‐spirogalbanone, and nor ‐α‐galbanone) were synthesized starting from Me2 SiCl2, (CH2 =CH)2 SiCl2, and Me2 (CH2 =CH)SiCl, respectively. These sila‐analogues proved to be less volatile and thus more tenacious than the parent carbon compounds while also providing insight into structure–odor correlations.